Relationship between the ratio of erythrocyte distribution width to albumin level and mortality in hypertensive population: Mediating role of inflammatory markers - Dongli Huang; Chun Zou; Hang Wu (PLoS ONE, 2025)
Background This study examined the ratio of erythrocyte distribution width (RDW) to albumin concentration (RAR) and all-cause, cardiovascular disease (CVD), and cancer mortality in the hypertension population, focusing on the role of inflammatory markers as mediators. Patients and methods Data from NHANES (1999–2018) were analyzed, linking National Death Index (NDI) records to mortality outcomes through December 31, 2019. A weighted sampling design categorized participants into three RAR groups. Cox regression models adjusted for demographic and clinical variables assessed the association between RAR and mortality outcomes. Mediation analyses explored the mediating role of the systemic Inflammatory response index (SIRI) and neutrophil-to-lymphocyte ratio (NLR). Results Among 26,935 participants with a median follow-up of 102 months and 6,007 deaths, elevated RAR was associated with increased risks of all-cause mortality (HR = 1.83, 95% CI: 1.76–1.90), cardiovascular disease mortality (HR = 1.81, 95% CI: 1.68–1.95), and cancer mortality (HR = 1.70, 95% CI: 1.55–1.86). Segmented regression showed a nonlinear relationship between RAR and all-cause mortality, cardiovascular mortality, and cancer mortality, and the threshold effect results showed a fold value of 4.10, with a greater HR when RAR < 4.10. Mediation analysis revealed that SIRI and NLR mediated the relationship between RAR and all-cause mortality by 8.12% and 6.00%, respectively. Conclusion In hypertensive populations, higher RAR values are associated with increased all-cause mortality, cardiovascular mortality, and cancer mortality. Inflammation partially mediates the relationship between RAR and all-cause mortality.